Vocational Orientation and the Need for Establishing Career Counselling Office in Vietnamese Schools - Giang, Thien-Vu; Tran, Luong; Huynh, Van-Son; Nguyen-Thi, Mai-Lan; Nguyen-Thi, Diem-My (Journal of Technical Education and Training, 2020)
School psychology is a field that has been receiving a lot of attention recently in Vietnam as it prepares to restructure the general education curriculum. In particular, vocational orientation and career counseling are most concerned due to the emergence of new subjects in the educational curriculum - Experimental and Vocational Orientation Activities. The objective of this study is to investigate the current situation of vocational orientation problems and the need for career counseling of Vietnamese high school students to provide evidence to develop the school counseling activities and the School Psychology in Vietnam. This is a quantitative study used a questionnaire to examine the current situation of vocational orientation problems and the need for career counseling of 1200 high school students in Vietnam to illustrate the importance of vocational orientation work. The results showed that Vietnamese high school students faced many vocational orientation problems and wanted support from school counselors. But the reality did not meet the needs of students: Vietnamese schools lacked a team of school counselors both in quality and quantity, also lack of school counseling offices in almost high schools. This result is expected to contribute to the development of the School Psychology in Vietnam, but firstly, to promote the establishment of counseling office at least one office per school.